2015
DOI: 10.1007/s13197-015-1953-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of white, yellow and purple maize flours and rheological characterization of their doughs

Abstract: White, yellow and purple maize flours were obtained after dried kernels milling with two different sieves (200 and 500 μm). Hygroscopic characteristics, particle size distribution, colour and total starch and damaged starch (DS) of flours were determined. Maize flour doughs were obtained by mixing of flour and water in a laboratory kneader (Mixolab®) at constant dough consistency (1.10 ± 0.07 Nm). Dough properties like water absorption (WA), development and stability times were determined. Rheological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…The L * , a * , and b * values of blue corn kernels indicated that their color was on the blue and purple scale (Table ) and they were measured as 26.52, 5.74, and 1.60, respectively. In a study the L * , a * , and b * color values of purple corn flour were reported as 53.80, 2.22, and 2.54, respectively (Moreira and others ). While the L * and b * color values of blue corn flour were lower, the a * value was higher than the results of the reported studies.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The L * , a * , and b * values of blue corn kernels indicated that their color was on the blue and purple scale (Table ) and they were measured as 26.52, 5.74, and 1.60, respectively. In a study the L * , a * , and b * color values of purple corn flour were reported as 53.80, 2.22, and 2.54, respectively (Moreira and others ). While the L * and b * color values of blue corn flour were lower, the a * value was higher than the results of the reported studies.…”
Section: Resultsmentioning
confidence: 94%
“…Corn is not only consumed as a whole kernel by human and animals, but it also used to produce flour, starch, sugar syrups, and oil in the food industry. Other industry branches, such as chemistry, pharmaceuticals, and cosmetics, utilize corn for different purposes (Moreira and others ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the market demand for gluten-free formulations has driven more research in the different steps leading from the maize kernel to the maize bread quality (e.g., Moreira et al, 2015 ; Garzón et al, 2017 ; Martínez and Gómez, 2017 ). In parallel, an increased investment on the improvement of open-pollinated maize populations has been driven by a renewed interest in materials traditionally used for ethnic food commodities and for their use in the context of more sustainable farming systems (e.g., Revilla et al, 2012 , 2015 ; Samayoa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rheology literature, it is also customary to consider the soecalled Burgers model, which consists of a Maxwell and a Kelvin materials in series (Malkin and Isayev, 2006;Morrison, 2001; Barnes et al, 1998). Indeed, this model is able to represent the rheological behavior of various materials as altered rock (Jiang et al, 2015), epoxy adhesive (Costa and Banos, 2015), asphalt mixture (Cai et al, 2013), thermoplastic polyurethane/organoclay nanocomposite (Ercan et al, 2017) or flour doughs (Moreira et al, 2015;Meerts et al, 2017). However, the Burgers model can require additional elements to represent a particular characteristic of the rheological behavior, as for instance an empirical expression for the stress hardening behavior of agar gels (Yu et al, 2012) or a plastic element for sandstone samples (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%